+0  
 
0
94
1
avatar

(k+1)(K-5)

Guest Mar 9, 2017

Best Answer 

 #1
avatar
+10

Expand the following:
(k + 1) (k - 5)

(k + 1) (k - 5) = (k) (k) + (k) (-5) + (1) (k) + (1) (-5):
k k + k - 5 k - 5

k k = k^2:
k^2 + k - 5 k - 5

k - 5 k = -4 k:
Answer: k^2 - 4k - 5

Guest Mar 9, 2017
 #1
avatar
+10
Best Answer

Expand the following:
(k + 1) (k - 5)

(k + 1) (k - 5) = (k) (k) + (k) (-5) + (1) (k) + (1) (-5):
k k + k - 5 k - 5

k k = k^2:
k^2 + k - 5 k - 5

k - 5 k = -4 k:
Answer: k^2 - 4k - 5

Guest Mar 9, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.